Five Steps Towards Avoiding Narrative Traps in Decision-Making - Dolan, Paul; Henwood, Amanda (Frontiers in Psychology, 2021)
Narratives provide simple rules about how we ought to live and what our priorities ought to be. They are especially appealing in times of high uncertainty. Using the uncertainty surrounding Covid-19 as an illustration, we show how a narrative to preserve life has become dominant, and we illustrate how it has been reinforced by several behavioural biases. We argue that being able to identify and critically evaluate the impact of dominant narratives is vital to ensuring optimal decision-making. To facilitate this, we offer five recommendations – the ABCDE of decision-making – that can help to reduce the “narrative trap” in decision-making in any uncertain environment.